Analisis Peran Ayah dan Ibu dalam Mengajarkan Pendidikan Seksual Kepada Anak sebagai Usaha Pencegahan Kekerasan Seksual terhadap Anak di Desa Telaga Murni - Devi Rahmi Fuadah; Oyoh Bariah; Achmad Junaedi Sitika (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Violence against children is a disgraceful act committed by adults or adults at the age and thought below children, thus preventing children from fulfilling their sexual needs. The impact of sexual violence on children in the form of physical, psychological and psychosocial children. Sexual violence against children does not only occur in the public sphere but can also occur in the family sphere. Families are diverse in society in which there are people such as mothers, fathers, and children who have different roles. Sexual education in the family is intended to foster a child's attitude of vigilance when the density of children begins to enter the community. This writing aims to show the extent to which the family plays a role in providing sexual education to children. In this paper, the descriptive qualitative method with analytical techniques uses data reduction techniques, data presentation and finally drawing conclusions. The results of this study indicate that each level of time or age of sexual education given to children is different, such as at the childhood level the provision of sexual education can be in the form of directions to recognize body organs and teach cleansing, but in language that is easily understood by children at their age. The level of adolescent sexual education that is not appropriate should be in accordance with the type and for adult level children, sexual education is more directed at giving direction or advice to go to a new life when the time comes.